FERILIZERS - Ranjan Kumar Basak; Ranjan Kumar Basak (Ludhiana Kalyani, 1999)
This book has been divided in to five parts and it involve manufacturing process of fertilizers and their properties
Fertilizer Testing Nitrogen Phosphorus Potassium
Keywords: Fertilizer Testing ,Nitrogen ,Phosphorus